Revisiting the ARI Programme of BRAC: how well are we doing? - Islam, Qazi Shafayetul; Ahmed, Syed Masud; Khan, Mohammed Abbas Uddin (BRAC Research and Evaluation Division (RED), 2019)
The ARI (Acute Respiratory Infection) control programme of BRAC has been in operation for the last few years. No independent evaluation has so far been conducted to explore how far the objectives of the programme have been achieved in terms of raising awareness among the health workers and community people, especially mother/caregivers about ARI, increasing capacity of health workers in managing ARI cases in the community, and changing health-seeking behaviour of mothers for appropriate and quick treatment. This is a cross-sectional population based study comparing groups with or without ARI programmes. The study was conducted in 30 upazilas where BRAC ARI control programme is being implemented since 2007. In addition, 10 upazilas were selected from adjacent programme areas to serve as control. The study included 2,800 mothers, 1,440 children with ARI symptoms, and 238 community health workers who were actively involved in the implementation of the ARI programme. The Shasthya shebikas (SS), frontline workers of BRAC, appeared to have insufficient knowledge about ARI, its prevention and other related information. Similarly, the level of awareness among mothers in terms of recognition of symptoms of ARI and its prevention remains inadequate. However, the awareness was higher in programme areas compared to non-programme areas. The majority of the mothers heard about the community-based BRAe ARI control programme, but they were unaware about the detail activities of the programme. The overall management of ARI with respect to diagnosis and treatment by the health workers especially SSs was not up to the expected level. They did not count the rate of respiration regularly while diagnosing different stages of pneumonia. The SSs did not tell mothers about the doses of co-trimmoxazole syrup in many cases, and about the danger symptoms and signs, and prevention of ARI further. Sixty percent of mothers would not seek ARI treatment from BRAC in programme areas. Mothers preferred to go to the village doctors and drug sellers in both the programme and non-programme areas. During health-seeking, one-fourth of the mothers did not seek treatment, and one-fourth received spiritual treatment. The knowledge of BRAC SSs and the mothers was not enough to deal with ARI management. Thus, it is difficult to expect quick management of ARI to save life of the children in the community. Many mothers still sought treatment from unqualified providers. Furthermore, the quality of management by BRAC SSs was not of expected level. So, we conclude that many children were at risk of mortality due to ARI. BRAG ARI programme should look into the matter seriously to achieve the programme goal, and to reduce child morbidity and mortality.